Multimoora optimization used to decide on a bank loan to buy property - Brauers, Willem Karel M.; Zavadskas, Edmundas Kazimieras (Technological and Economic Development of Economy, 2011)
Different multiple objectives are expressed in different units, which makes optimization difficult. Therefore the internal mechanical solution of a Ratio System, producing dimensionless numbers, is preferred to Weights which are most of the time used to compare the different units. In addition, the ratio system creates the opportunity to use a second approach: a non-subjective Reference Point Theory. The two approaches form a control on each other. The choice of the objectives is even more non-subjective if the opinion of all stakeholders interested in the issue is involved by the use of the Ameliorated Nominal Group and Delphi Techniques. The overall theory is called MOORA (Multi-Objective Optimization by Ratio Analysis). The results are still more convincing if a Full Multiplicative Form is added to MOORA under the name of MULTIMOORA. At that moment the control by three different approaches forms a guaranty for a solution being as non-subjective as possible. MULTIMOORA is used to decide upon a bank loan to buy property.